2014
DOI: 10.1155/2014/698263
|View full text |Cite
|
Sign up to set email alerts
|

Ripening of Sudanese Braided (Muddaffara) Cheese Manufactured from Raw or Pasteurized Milk: Effect of Heat Treatment and Salt Concentration on the Physicochemical Properties

Abstract: The objective of the study was to investigate the interactive effect of heat treatment (raw or pasteurized milk), ripening in salted whey (SW) and storage period for up to 3 months on the physicochemical properties of Sudanese braided cheese (SBC). Braided cheeses were manufactured from raw (BCRM) and pasteurized (BCPM) milk and ripened in SW (0%, 5%, and 10% salt) for up to 90 days. All the treatments significantly (P ≤ 0.05) affected the physicochemical characteristics of SBC. The total solid, protein, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…However this study showed a decrease in the ash content of Mudaffara cheese during the storage (Table 2). The results are in disagreement with those who reported that the ash content of cheese increased as the storage period progressed (Altahir et al 2014).…”
Section: Ash Contentcontrasting
confidence: 99%
See 1 more Smart Citation
“…However this study showed a decrease in the ash content of Mudaffara cheese during the storage (Table 2). The results are in disagreement with those who reported that the ash content of cheese increased as the storage period progressed (Altahir et al 2014).…”
Section: Ash Contentcontrasting
confidence: 99%
“…The reason for the increase could be due to the loss of the moisture content from the cheese, while the reduction that occurred after week 2 might because of refrigerating storage of the cheese. However Altahir et al (2014) and Farah and El Zubeir (2020) found that the protein content of Mudaffara cheese was found to decrease significantly during storage. The reduction in protein content was possibly due to the activity of proteolytic microorganisms leading to protein degradation.…”
Section: Fat Contentmentioning
confidence: 96%
“…Braided cheese was manufactured according to Altahir et al (2014). Briefly, the obtained fresh cow milk (10 kg) was divided in two equal portions.…”
Section: Cheese Manufacturementioning
confidence: 99%
“…The results showed that the higher fermentation temperature resulted in a more marked reduction in cell numbers and reflected the reduction in pH of the medium due to lactic acid production. The addition of spices was an added stress on the cells and may have led to more inhibition at the higher temperature of 43 • C. Althair et al [52] indicated that heat treatment had effects on the physicochemical properties of bacteria during mudafra cheese ripening. With emerging drug and acid-resistant microorganisms in recent years, natural antimicrobials that can act synergistically are crucial in controlling foodborne pathogens.…”
Section: Discussionmentioning
confidence: 99%